ANALISIS TERHADAP KESEIMBANGAN PERLINDUNGAN HAK CIPTA DAN KEPENTINGAN EKONOMI PELAKU USAHA DALAM PEMUNGUTAN ROYALTI MUSIK - Indra Jaya; Appe Hutauruk; Mardiman Sane (LPPM STIH Awang Long, 2026)
The enactment of Government Regulation Number 56 of 2021 concerning the Management of Copyright Royalties for Songs and/or Music represents a significant step toward strengthening the protection of the economic rights of creators and copyright holders in Indonesia. However, its implementation has raised legal issues regarding the determination of royalty-paying business actors, overlapping royalty obligations, and the balance between copyright protection and business interests in the digital era. This study aims to analyze the legal framework governing music royalty collection, evaluate whether the current system reflects the principles of justice, legal certainty, and proportionality, and formulate a fair limitation of royalty-paying subjects. The research employs a normative juridical method supported by a socio-legal approach through statutory, conceptual, comparative, case, and socio-legal analyses. The findings indicate that the existing regulatory framework does not clearly classify commercial music users, creating legal uncertainty and the potential imposition of disproportionate royalty obligations on businesses that use music only as a supporting element of their activities. Accordingly, this study proposes a reformulated royalty system that classifies users into Primary Users and Secondary Users based on the extent of direct economic benefit obtained from musical works. This approach is expected to promote a more balanced, equitable, and proportionate royalty management system while ensuring effective copyright protection and supporting sustainable business activities.